2013
DOI: 10.1177/8756087913498402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aragonite calcium carbonate on barrier and mechanical properties of a three-layer co-extruded blown low-density polyethylene film

Abstract: The study is aimed to find whether the location of the calcium carbonate added in a three-layer co-extruded blown film has an impact on film's barrier and mechanical properties. Aragonite calcium carbonate-added low-density polyethylene films were produced at various weight ratios and layer structure through a three-layer co-extrusion blown film line. The scanning electron microscopy micrographs were obtained to understand the dispersion on the calcium carbonate and the morphology related to the film barrier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Many studies investigated the advantages of blending calcium carbonate into polymers. However, its agglomeration enormously decreases the composite's physical properties, limiting its applications [12]. Conventional surface modification by solution coating can involve interactions between chitosan with calcium carbonate to induce the calcium carbonate's nucleation on the chitosan-coated surfaces [13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies investigated the advantages of blending calcium carbonate into polymers. However, its agglomeration enormously decreases the composite's physical properties, limiting its applications [12]. Conventional surface modification by solution coating can involve interactions between chitosan with calcium carbonate to induce the calcium carbonate's nucleation on the chitosan-coated surfaces [13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ), one of promising filler materials for plastics, paper, lubricants, paints and pigments , has three polymorphs including rhombohedral calcite, orthorhombic aragonite, and hexagonal vaterite . It is reported that the metastable aragonite CaCO 3 nanoparticles with needle‐like shape show the superior performance as the filler in paper , polyvinyl alcohol or polypropylene composites and PVC , comparing with the calcite and vaterite partners.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Some techniques have been employed to realize the controllable growth of aragonite CaCO 3 . The existing synthetic approaches can be divided into two categories: (1) slow precipitation in the presence of an additive as the control agent, and (2) synthesis in water−organic solvent systems. 19−22 Inorganic additives containing ions such as Sr 2+ , Ba 2+ , Pb 2+ , and Mg 2+ are added to the solution of soluble calcium salts for controlling the growth of aragonite CaCO 3 at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ), one of the most widely existing minerals in nature, has been extensively used in rubber, plastic, printing ink, dope, toothpaste, cosmetics, and food industries. CaCO 3 has three different crystalline forms: calcite, aragonite, and vaterite. , Aragonite CaCO 3 in the form of a needle-like crystal is regarded as a functional inorganic material that can alter the optical and mechanical properties of pigment, plastics, and paints. Especially in biologic systems, the crystal lattice of aragonite can be stable with the existence of amino acids in microenvironments, which makes aragonite CaCO 3 a possible biomedical material in the future. However, among these three anhydrous polymorphs, calcite is the most stable, while aragonite and vaterite are the metastable and unstable forms of CaCO 3 , respectively. To keep the continuous growth of aragonite CaCO 3 , it is necessary to ensure that the concentrations of the ions are within the metastable region (between the saturation and supersaturation curves), as shown in Figure . Q C is the corresponding ion product, which is represented as where [Ca 2+ ] and [CO 3 2– ] are the concentrations of Ca 2+ and CO 3 2– , respectively.…”
Section: Introductionmentioning
confidence: 99%